2007
DOI: 10.1007/s00253-007-0853-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of different types of mannosylerythritol lipids as biosurfactants by the newly isolated yeast strains belonging to the genus Pseudozyma

Abstract: Mannosylerythritol lipids (MEL), which are abundantly secreted by yeasts, are one of the most promising biosurfactants known. To obtain various types of MEL and to attain a broad range of applications for them, screening of novel producers was undertaken. Thirteen strains of yeasts were successfully isolated as potential MEL producers; they showed high production yields of MEL of around 20 g l(-1) from 40 g l(-1) of soybean oil. Based on the taxonomical study, all the strains were classified to be the genus Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 35 publications
3
62
0
Order By: Relevance
“…KM-160 19) used in this study were isolated as MEL-A and MEL-B producer respectively, as reported previously. Pseudozyma tsukubaensis JCM 10324…”
Section: Microorganismsmentioning
confidence: 99%
See 4 more Smart Citations
“…KM-160 19) used in this study were isolated as MEL-A and MEL-B producer respectively, as reported previously. Pseudozyma tsukubaensis JCM 10324…”
Section: Microorganismsmentioning
confidence: 99%
“…The concentrated glycolipids were dissolved in chloroform and then purified by silica gel (Wako-gel C-200) column chromatography with a gradient elution of a chloroform/acetone (10:0 to 0:10, v/v) mixture as solvent system. 19) The purified glycolipids were used in subsequent experiments.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations